2014
DOI: 10.1007/s10557-014-6547-4
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids as an Emerging Pharmacologic Agent for Cardiopulmonary Resuscitation

Abstract: Although cardiac arrest (CA) constitutes a major health problem with dismal prognosis, no specific drug therapy has been shown to improve survival to hospital discharge. CA causes adrenal insufficiency which is associated with poor outcome and increased mortality. Adrenal insufficiency may manifest as an inability to increase cortisol secretion during and after cardiopulmonary resuscitation (CPR). Several studies suggest that glucocorticoids during and after CPR seem to confer benefits with respect to return o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 109 publications
2
30
0
Order By: Relevance
“…The administration of corticosteroids during cardiac arrest has been proposed for decades; however, there is no strong evidence to support the efficacy of steroids to improve the outcomes of resuscitation[ 7 , 19 ]. Recent studies have described cardiac arrest-related adrenal insufficiency, finding that the condition was associated with increased mortality[ 19 , 20 ]. Ito et al [ 20 ] reported that cortisol levels were moderately low during and after cardiac arrest and CPR, which suggests impairment of adrenal function.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of corticosteroids during cardiac arrest has been proposed for decades; however, there is no strong evidence to support the efficacy of steroids to improve the outcomes of resuscitation[ 7 , 19 ]. Recent studies have described cardiac arrest-related adrenal insufficiency, finding that the condition was associated with increased mortality[ 19 , 20 ]. Ito et al [ 20 ] reported that cortisol levels were moderately low during and after cardiac arrest and CPR, which suggests impairment of adrenal function.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found that the total plasma cortisol levels were signi cantly higher in patients who experienced CA but ACTH levels were not. High levels of in ammatory cytokines inhibit ACTH release [19]. During critical illness, the body does not su ciently metabolize cortisol [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of GC during resuscitation improves the survival rate of patients who experienced CA due to its direct anti-in ammatory, immunosuppressive effects, hemodynamic, and positive inotropic effects. All of this ultimately leads to increased stress capacity of the body [19,20]. GC can activate GRs in cells when the body is under stress, thereby increasing both the effectiveness of resuscitation and the discharge survival rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCY blocks the mitochondrial permeability transition pore thereby preventing apoptosis and cell death [10] and improving contractility [11, 12], while MP decreases macrophage and leukocyte activation [13]. Both agents also decrease inflammatory cytokine production [10, 1419].…”
Section: Introductionmentioning
confidence: 99%